(STUDI LITERATUR) PENGGUNAAN MODEL MIND MAP PADA PEBELAJARAN GEOGRAFI DI SEKOLAH DASAR - Aina Ansa Zulfa; Muh. Husen Arifin; Yona Wahyuningsih (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
This article discusses the Mind Mapping method that can improve students' ability to be active in class. The purpose of this article is to find out that the Mind Mapping method can increase student activity in the classroom. Activeness here means that the role of students is very influential on learning in the current curriculum, that learning must be student center and the teacher here is only a facilitator. With the use of Mind Mapping, it is hoped that students will not feel bored with memorizing subjects, and with the use of Mind Mapping it will make it easier for students to memorize learning theories. Through mind mapping, students are expected to be able to express their opinions, be interactive, and think imaginatively with the aim of freeing students from memorization that is comfortable for them. Therefore, by using the Mind Mapping method, students can change their habits. At first they only paid attention to the teacher, but now they are required to be more active in each lesson.Keywords: Learning, Method, Mind Mapping